Multi-Omics Approaches for Exploring Health Implications: A Review - Siddiqui, Nadeem (Asian Journal of Pharmaceutics (AJP), 2023)
The concept of metabolic regulations deals with the varied and innumerable metabolic pathways that are present in the human body. A combination of such metabolic reactions paves the way to the proper functioning of different physiological and biological processes. Dealing with the adversities of a disease, the engineering of novel metabolic pathways showcases the potential of metabolic engineering and its application in the therapeutic treatment of diseases. A proper and deeper understanding of the metabolic functions in the human body can be known from simulated yeast models. The current review gives a brief understanding of the interactions between the molecular set of metabolomes and their complexity.